SITTING TIME AND SPORT PARTICIPATION OF THE EMPLOYED POPULATION IN HUNGARY AND EUROPE - Alexandra MAKAI; Viktória PRÉMUSZ; Kinga LAMPEK; Pongrác ÁCS; Ágnes SIMON-UGRON; Mária FIGLER (Cluj University Press, 2018)
Introduction. The aim of our study was to examine the participation, motivation and locations of sport activity of adult employed population in Hungary and Europe, highlighting the differences in sport participation among different occupation groups. Methods. The Eurobarometer (EB) is a set of international surveys conducted on behalf of the European Commission. The survey consisted of two modules, the 'Standard EB' which contains the core set of questions which are similar in every survey, and the 'Special EB' which included physical activity (PA) and sitting time (ST). In our research we used the Eurobarometer 2013 database. Results. According to ST we found significant differences between the European and Hungarian employed adults. Hungarian respondents spent less time with sitting. The proportion of respondents not doing any sports is the highest among Hungarian women (67,44%, CI: 64,24 - 70,64), and those who's occupation is "supervisor", "unskilled or skilled manual worker", or whose job is an "employed position - travelling" or "employed position at desk" (62,64% (CI: 55.58 - 69.70) -72,41% (CI: 64,11-80,71). Conclusion. Our results show that more than one-third of Hungarian employees do not do regular sports, but overall spend less time sitting than the EU average. The amount of sitting and the proportion of inactive respondents is higher among women. Based on our analysis of job types we highlight office administrators' work - with higher rate of females -which includes very little PA. Thus, the increase of PA among women and among administrative workers is the key focus of our further research.